SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN UMKM TERBAIK MENGGUNAKAN METODE PREFERENCE SELECTION INDEX - Abdillah, Ihsan; Bangun, Budianto; Sihombing, Volvo (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
This study aims to design and implement a Decision Support System (DSS) based on the Preference Selection Index (PSI) method to determine the best Micro, Small, and Medium Enterprises (MSMEs) products in Bagan Sari Village, Labuhan Batu Selatan Regency. The main problem addressed is the need for a fair and objective mechanism to assess MSME products based on five key criteria: price, quality, popularity, innovation, and contribution to the village economy. This system is designed to assist the village government in prioritizing support for MSMEs with superior products, thereby significantly impacting the local economy. Through data analysis stages, the system successfully identified the top three alternatives: UMKM_07, UMKM_04, and UMKM_08, which scored the highest in the assessment criteria. These results demonstrate that the PSI method can provide objective and transparent recommendations. By implementing this DSS, the village government can allocate resources more effectively, support MSMEs in enhancing competitiveness, and drive local economic growth. This research is expected to serve as a reference for other villages in managing and advancing MSMEs in a measurable and efficient manner.